2015
DOI: 10.1007/s00216-015-8623-4
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying amyloid fibrils in protein mixtures via infrared attenuated-total-reflection spectroscopy

Abstract: Amyloid aggregation of proteins is usually associated with amyloid diseases. A distinct feature of protein aggregation is the increase of crossed β-sheet structures. Infrared attenuated-total-reflectance (IR-ATR) spectroscopy is a sensitive optical technique that has the potential to provide secondary structure characteristics of proteins even in complex biological samples. In this study we report the analysis of secondary structures of proteins, using the amide I band for the detection and quantification of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…On the other hand, γ‐globulin is rich in β‐sheet structures, and the amide I band is correspondingly more pronounced at approximately 1639 cm −1 . These results are in agreement with previous studies carried out on silicon ATR waveguides .…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…On the other hand, γ‐globulin is rich in β‐sheet structures, and the amide I band is correspondingly more pronounced at approximately 1639 cm −1 . These results are in agreement with previous studies carried out on silicon ATR waveguides .…”
Section: Resultssupporting
confidence: 94%
“…Protein spectra analyzed with the conventional FTIR spectrometer were subject to a similar treatment routine, as previously described . IR spectra were acquired and processed with Opus 6.5 software, which was also used to exclude water vapor and CO 2 interferences.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the aggregation state of α-synuclein or amyloid β (Aβ) peptides, which are both associated with neurodegenerative diseases such as Parkinson's or Alzheimer's, have been studied via MIR spectroscopy (110). Probing mechanistic details of misfolding and fibrillation (122,123), as well as the inhibition of these processes, along with potential environmental influences and stimulants has revealed band shifts characteristic of the amide I (1,600-1,700 cm −1 ) and amide II (1,500-1,600 cm −1 ) features of proteins, which may be assigned to α-helix or β-sheet conformations (124,125).…”
Section: Liquid Phase: Biomedical Applications and Process Monitoringmentioning
confidence: 99%
“…The sensitivity to individual secondary structure elements originates in differing patterns of hydrogen bonding, dipole-dipole interactions and geometric orientations in the α-helices, β-sheets, turns and random coil structures that induce different frequencies of the C=O vibrations [4]. It has been shown that based on the analysis of the amide I band, quantitation of individual proteins in a protein mixture can be performed [47].…”
Section: Introductionmentioning
confidence: 99%